Pengaruh Budaya Kerja, Kompensasi, dan Motivasi Kerja Terhadap Kepuasan dan Kinerja Karyawan PT. Paramount Enterprise International - Dwi Sri Dani Afriza; Lukman Krisna Adi Putra (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Human resources are a very important part of a company to grow and excell in its business. The reason for this research to be conducted is becasue only limited research has been to study the influence of work culture, compensation, and work motivation on job satisfaction and employee performance. The researcher used a quantitative research approach. This study used a Slovin sample of 92 people from a population of all employees at PT. Paramount Enterprise International, totaling 1,220 people. The technical analysis of the primary data from questionnaire results includes instrument testing, classical assumption testing, and hypothesis testing. Data processing is performed using the SPSS-22 and the research results indicates that work culture, compensation, and motivation have positive and significant effect on job satisfaction. Work culture, compensation, and motivation also have a positive and significant effect on performance. Simultaneously, work culture, compensation, and work motivation have a positive and significant effect on job satisfaction and performance.